PEMBELAJARAN SOSIAL EMOSIONAL TERHADAP MOTIVASI BELAJAR PESERTA DIDIK DI SEKOLAH DASAR - Ricky Avandra; Neviyarni S; Irdamurni (STKIP Subang, 2023)
Social and emotional learning is motivated by the belief that it is not enough for students to only develop their academic abilities. However, social and emotional aspects must also be developed. Various research results show that social-emotional competence plays an important role in learning and success in one's life. As an educator who is directly related to participants in school, he can see the low learning motivation of students as a result of the lack of implementation of social emotional learning carried out in classroom learning. This study aims to motivate students in learning through emotional social learning. This research uses library/literature research where data is obtained from literature reviews of various relevant journals, book reviews and others. Data after review will be concluded according to the problem being studied. The aim of the research is to provide understanding and knowledge about social emotional learning in learning to be able to increase students' motivation in learning. Data collection was carried out by looking for various literature studies, articles/journals that were relevant to the title of the study under study..